2018
DOI: 10.1051/shsconf/20184610004
|View full text |Cite
|
Sign up to set email alerts
|

Le langage oral en production chez les enfants bilingues : quels liens avec l’exposition ?

Abstract: L’objectif de cette étude est d’observer les effets de l’exposition aux langues sur différentes variables linguistiques en production orale d’enfants bilingues français/anglais sans pathologie, scolarisés dans une école internationale publique (France), et répartis en deux groupes d’âges (groupe 1 : N = 10, M = 6;3; groupe 2 : N = 15, M = 10;2). Des questionnaires parentaux ont permis d’obtenir des mesures quant à l’exposition courante et cumulative aux langues ainsi qu’à la fréquence à laquelle les enfants li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Our data add further support to previous research findings that have indicated a strong association between amount of exposure and narrative microstructure skills (Bedore et al, 2010;Cohen & Mazur-Palandre, 2018;Pearson, 2002;Rodina, 2017;Rojas & Iglesias, 2013). Furthermore, children used more low frequency vocabulary in the language in which they were read to more often (cf.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data add further support to previous research findings that have indicated a strong association between amount of exposure and narrative microstructure skills (Bedore et al, 2010;Cohen & Mazur-Palandre, 2018;Pearson, 2002;Rodina, 2017;Rojas & Iglesias, 2013). Furthermore, children used more low frequency vocabulary in the language in which they were read to more often (cf.…”
Section: Discussionsupporting
confidence: 90%
“…Using oral narratives generated in each language from identical images enables researchers to compare multiple performance measures within and across two languages in a single ecological task. Previous studies have indicated that microstructure elements, such as vocabulary and morphosyntax, are more language specific, depend on proficiency in each language, and relate to language exposure (Cohen & Mazur-Palandre, 2018;Pearson, 2002;Rodina, 2017;Rojas & Iglesias, 2013). Several linguistic microstructure measures are pertinent for the analysis of children's narratives, including lexical productivity measured, by the number of different words (e.g., Cohen & Mazur-Palandre, 2018;Pearson, 2002;Rodina, 2017;Rojas & Iglesias, 2013;Simon-Cereijido & Gutiérrez-Clellen, 2009) and morphosyntactic accuracy (e.g., Bedore et al, 2010;Cohen & Mazur-Palandre, 2018;Pearson, 2002;Rodina, 2017).…”
Section: Narrative Developmentmentioning
confidence: 99%
See 1 more Smart Citation